Cost-Effectiveness of Frontline Treatment for Advanced Renal Cell Carcinoma in the Era of Immunotherapies - SiNi Li; SiNi Li; JianHe Li; LiuBao Peng; YaMin Li; YaMin Li; XiaoMin Wan (Frontiers Media S.A., 2021)
Background: Recent randomized controlled trials have demonstrated that immune checkpoint inhibitors (ICIs) improve patient outcomes, but whether these novel agents are cost-effective for untreated advanced renal cell carcinoma (aRCC) remains unclear.Materials and Methods: A microsimulation model was created to project the healthcare costs and outcomes of six strategies (lenvatinib-plus-pembrolizumab, nivolumab-plus-cabozantinib, nivolumab-plus-ipilimumab, pembrolizumab-plus-axitinib, avelumab-plus-axitinib, and sunitinib monotherapy) for patients with aRCC. Transition probability of patients was estimated from CLEAR, CheckMate 9ER, CheckMate 214, KEYNOTE-426, JAVELIN Renal 101, and other data sets by using parametric survival modeling. Lifetime direct medical costs, life years (LYs), quality-adjusted LYs (QALYs), and incremental cost-effectiveness ratios (ICERs) were estimated from a United States payer perspective. One-way and probabilistic sensitivity analyses were performed, along with multiple scenario analyses, to evaluate model uncertainty.Results: Of the six competing strategies, nivolumab-plus-cabozantinib yielded the most significant health outcomes, and the sunitinib strategy was the least expensive option. The cost-effective frontier consisted of the nivolumab-plus-cabozantinib, pembrolizumab-plus-axitinib, and sunitinib strategies, which displayed the ordered ICERs of $81282/QALY for pembrolizumab-plus-axitinib vs sunitinib and $453391/QALY for nivolumab-plus-cabozantinib vs pembrolizumab-plus-axitinib. The rest of the strategies, such as lenvatinib-plus-pembrolizumab, nivolumab-plus-ipilimumab, and avelumab-plus-axitinib, were dominated. The cost of sunitinib drove the model most influentially.Conclusions: For aRCC, the pembrolizumab-plus-axitinib strategy is likely to be the most cost-effective alternative at the willingness-to-pay threshold of $100,000.